Outcomes of ventricular tachycardia ablation in patients with ischemic and non-ischemic cardiomyopathy: A propensity score matched analysis - Gomes, DA (2024)
Introduction and objectives: Catheter ablation (CA) is effective in the treatment of ventricular tachycardia (VT). Although some observational data suggest patients with non-ischemic cardiomyopathy (NICM) have less favorable outcomes when compared to those with an ischemic etiology (ICM), direct comparisons are rarely reported. We aimed to compare the outcomes of VT ablation in a propensity score matched population of ICM or NICM patients. Methods: Single-center retrospective study of consecutive patients undergoing VT ablation from 2012 to 2023. A propensity score (PS) was used to match ICM and NICM patients in a 1:1 fashion according to age, sex, left ventricular ejection fraction (LVEF), NYHA class, electrical storm (ES) at presentation, and previous endocardial ablation. The outcomes of interest were VT-free survival and all-cause mortality. Results: The PS yielded two groups of 71 patients each (mean age 63±10 years, 92% male, mean LVEF 35±10%, 36% with ES at presentation, and 23% with previous ablation), well matched for baseline characteristics. During a median follow-up of 2.3 (interquartile range IQR 1.3-3.8) years, patients with NICM had a significantly lower VT-free survival (53.5% vs. 69.0%, log-rank P=0.037), although there were no differences regarding all-cause mortality (22.5% vs. 16.9%, log-rank P=0.245). Multivariate analysis identified NICM (HR 2.34 [95% CI 1.32-4.14], P=0.004), NYHA class III/ IV (HR 2.11 [95% CI 1.11-4.04], P=0.024), and chronic kidney disease (HR 2.23 [95% CI 1.25-3.96], P=0.006), as independent predictors of VT recurrence.